2010
DOI: 10.1007/s00276-010-0704-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicted cervical canal enlargement and effective cord decompression following expansive laminoplasty using cervical magnetic resonance imaging

Abstract: Laminoplasty may produce larger canal expansion at the lower cervical spine compared to the upper cervical area; therefore, the outcomes of those who have predominantly higher cervical myelopathy were inferior to those who have lower cervical myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Indirect decompression of the anterior aspect of the spinal cord is achieved by posterior drift of the spinal cord. 17,18 It was previously believed that whether a sufficient expansion of the spinal canal with an effective spinal cord drift is achieved would directly affect the outcome of these posterior treatments. 19 In previous studies, the extent of decompression by laminoplasty or laminectomy and fusion has not been compared effectively due to the lack of a measurement available.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect decompression of the anterior aspect of the spinal cord is achieved by posterior drift of the spinal cord. 17,18 It was previously believed that whether a sufficient expansion of the spinal canal with an effective spinal cord drift is achieved would directly affect the outcome of these posterior treatments. 19 In previous studies, the extent of decompression by laminoplasty or laminectomy and fusion has not been compared effectively due to the lack of a measurement available.…”
Section: Discussionmentioning
confidence: 99%
“…This anatomical variance can be determined precisely and accurate instrumental sizing can then be determined and develop to comply with the limitations [1,6]. In addition, it may also help in predicting the outcomes of the new procedure [26]. Even though a cadaveric study gives more actual operative setting, it can be limited due to its availability and strict ethical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors measured the spinal cord shift after expansive laminoplasty. Yusof et al 26 reported that the difference in the space anterior to the cord between before and after expansive laminoplasty ranged from 8.6 to 10.9 mm. Sodeyama et al 27 reported that the spinal cord shift ranged from 0 to 6.6 mm, whereas Kong et al 28 reported that the peak anterior subarachnoid space was 6.9 mm in patients undergoing expansive laminoplasty from C3 to C7.…”
Section: E498mentioning
confidence: 99%